Case Report: Milliary TB in Adolescence Diagnosed in Tapin, South Kalimantan, A Call for TB Awereness - Trilaksono, Rony; Sari, Karina Mayang (Syntax Literate, 2024)
This case report presents the clinical scenario of a 15-year-old adolescent admitted to the emergency room with complaints of shortness of breath and a persistent productive cough for the past 3 weeks, despite over-the-counter medication. The cough did not improve with over-the-counter medication. He also sometimes noticed blood stains in his phlegm. During the physical examination, a BCG scar was found on the right upper arm. The results showed that positive HIV status and the absence of BCG scars were significantly associated with miliary TB and extrapulmonary TB. However, in this case, both factors were not detected. The treatment regimen for miliary TB requires therapy for a minimum of 12 months, but teenagers experience difficulties in undergoing therapy due to the consumption of illegal drugs every day for a long period of time. Apart from that, social isolation and disrupted daily activities are also challenges for teenagers. The death rate from miliary TB in children reaches 15-20%, highlighting the importance of awareness of this disease. Therefore, handling and treating TB in adolescents requires special attention and further efforts to reduce the risk of treatment failure. Awareness of TB, especially in adolescents with chronic respiratory symptoms, must be increased to overcome this challenge in the future.